High and Frequent Dose of Dexlansoprazole and Amoxicillin Dual Therapy for Helicobacter pylori Infections: A Single Arm Prospective Study - Park, Hye Yoon; Kang, Eun Jeong; Kim, Dong Gun; Kim, Ki Ju; Choi, Jin Woo; Nam, Su Youn; Kwon, Yong Hwan; Lee, Hyun Seok; Jeon, Seong Woo (The Korean journal of gastroenterology, 2017)
Recently, the eradication rate of ( ) infection has decreased to less than 80% worldwide with the use of clarithromycin-based triple therapy owing to the increased resistance of to antibiotics, especially clarithromycin and metronidazole. This prospective study aimed to determine eradication rate of following high and frequent doses of extended-release dexlansoprazole and amoxicillin, as a dual therapy in a region with high clarithromycin resistance rate. A total of 50 treatment-naïve patients with active infections, who were confirmed through via rapid urease test or histology and serology between November 2015 and February 2016 at our hospital, were included for analysis. All enrolled patients were treated with 750 mg amoxicillin and 30 mg dexlansoprazole, four times a day for a total duration of 14 days. Treatment success was determined using urea breath test four weeks after treatment completion. Seven out of the 50 patients (29 men and 21 women; mean age, 57 years) dropped out during the study. The total eradication rate was 52% (26/50), and that for those with a compliance rate of over 90% was 68.4% (26/38). infections were not successfully eradicated in patients with a compliance rate of less than 90%. Nine patients (18%) reported side effects, such as mild diarrhea and abdominal fullness. No significant factors, such as smoking and alcohol consumption, affected the infection the eradication rate. High and frequent doses of proton pump inhibitor-amoxicillin dual therapy were not effective in eradicating infection in a province with high clarithromycin resistance rate.